ChemInform Abstract: Experimental and Theoretical Investigations on Structural and Vibrational Properties of Melilite‐Type Sr2ZnGe2O7 at High Pressure and Delineation of a High‐Pressure Monoclinic Phase. Issue 36 (September 2015) - Achary, S. Nagabhusan; Errandonea, Daniel; Santamaria‐Perez, David; Gomis, Oscar; Patwe, Sadiqua J.; Manjon, Francisco Javier; Hernandez, Placida Rodriguez; Munoz, Alfonso; Tyagi, Avesh Kumar
Abstract The title compound is characterized by high‐pressure powder XRD and Raman scattering measurements up to 22 GPa, and by DFT calculations.